Use of incineration fly ash as a substitute for cement in geotechnical applications - Chong, Timothy Mun Hou (Nanyang Technological University, 2022)
Singapore’s waste disposal trends have been on the rise in the last decade. The current primary solution for waste disposal is through incineration, that can reduce the waste volume by up to 90%. As a by-product of incineration, incineration fly ash has little usage currently, and is often transported to Singapore’s only landfill to rest.